Intermittent micafungin for prophylaxis in a rat model of chronic Candida albicans gut colonization. (28th July 2020) - Warn, Peter; Thommes, Pia; Sharp, Andrew; Sattar, Abdul; Undre, Nasrullah; Palacios-Fabrega, Jose Alejandro; Karas, Andreas
Abstract: Background: During antifungal prophylaxis, micafungin is generally infused IV once daily over 1 h. In practice, less-frequent dosing could improve the quality of life in patients requiring long-term treatment or prophylaxis. The feasibility of this approach was assessed using humanized doses of daily or infrequent micafungin regimens. Objectives: To evaluate the effectiveness of intermittent high-dose micafungin, simulating human exposure, for prophylaxis of invasive candidiasis in a rat model of chronic Candida albicans gastrointestinal colonization and systemic dissemination. Methods: Two weeks post-infection with an oral challenge of C. albicans, Sprague–Dawley rats were immunocompromised with a cytotoxic drug and a steroid. Rats received IV infusions of: daily vehicle control; daily subcutaneous micafungin (20 mg/kg SC); high-dose micafungin (20 mg/kg bolus SC + 80 mg/kg infusion/72 h, to simulate intermittent human dosing of 300 mg/72 h); or daily fluconazole by mouth (10 mg/kg PO). The effects of antifungal prophylaxis on faecal fungal burden and systemic C. albicans dissemination were evaluated. Results: A rat model of chronic C. albicans gastrointestinal colonization and systemic dissemination was established, characterized by a sustained microbiological burden over 29 days and fungal recovery from normally sterile tissues. Using this model, intermittent high-dose micafungin (delivered via iPrecio pumps) to simulate humanized doses of 300 mg/72 h was significantly more effective than vehicle control, as effective as once-daily micafungin and similar to daily fluconazole at reducing faecal burden and preventing systemic dissemination. Conclusions: These data indicate that intermittent high-dose micafungin can be as effective as daily therapy, supporting clinical assessment in high-risk patients requiring long-term antifungal prophylaxis.